Wave after wave: Contagion risk from commodity markets - Bernardina Algieri; Arturo Leccadito (University of Bonn, Center for Development Research (ZEF), 2017)
The aim of this study is to investigate the possible contagion risk coming from energy, food and metals commodity markets and to assess risk spillovers from biofuel to food commodity markets and from crude oil to food markets. To this purpose, we use the delta Conditional Value-at-Risk CoVaR) approach recently proposed by Adrian and Brunnermeier (2016) based on quantile regression. This novel methodology allows us first to identify a measure of contagion risk for energy, food and metals commodity markets, then to detect whether the risk contribution for a given market is significant, while distinguishing between tail events driven by financial factors, economic fundamentals or both, and finally, to assess whether the contagion effect of one market is significantly larger than the one of another market. The results show that energy, food and metals commodity markets transmit contagion within markets and there are spillovers from crude oil and biofuel to food markets. In particular, oil is systemically riskier than the other markets in causing economic instability. Oil is also more important than biofuel in affecting food markets. It emerges that contagion risk is mainly triggered by financial factors for energy and metal markets, while financial and economic fundamentals are relevant for food markets.
Keywords: F37; G15; Q14; Q43; 330; commodity markets; contagion risk; ∆CoVaR